Scratching behaviour and its features: a questionnaire-based study in an Italian sample of domestic cats. Issue 10 (October 2013) - Mengoli, Manuel; Mariti, Chiara; Cozzi, Alessandro; Cestarollo, Elisa; Lafont-Lecuelle, Céline; Pageat, Patrick; Gazzano, Angelo
Scratching behaviour in cats is described as a normal expression of the feline ethogram, having different possible purposes related to visual and chemical communication. During behavioural consultations owners often mention scratching as an additional problem. This preliminary study aimed to understand the characteristics of this complex behaviour by examining the variables displayed by a sample of the Italian feline population using multiple correspondence analysis. One hundred and twenty-eight cats were screened by means of a questionnaire to identify features of their scratching behaviour. Our data showed the importance of both the presence/absence of a scratching post in the cat's living area and its relationship to marking. When a scratching post is present in a cat's living area, the cat appears to use it. Some aspects related to sex, neutering, age and environmental characteristics may modify the expression of scratching as a marking behaviour. Research has led to increased knowledge of this behaviour and may help veterinarians in describing to owners why it is important for cats to express scratching behaviour in their environment. Such information could help veterinarians and owners to recognise normal and problematic scratching behaviours.